Chronic Kidney Disease and Cancer: Inter-Relationships and Mechanisms - Hu, Mengsi; Wang, Qianhui; Liu, Bing; Ma, Qiqi; Zhang, Tingwei; Huang, Tongtong; Lv, Zhimei; Wang, Rong (Frontiers in Cell and Developmental Biology, 2022)
Chronic kidney disease (CKD) has been recognized as an increasingly serious public health problem globally over the decades. Accumulating evidence has shown that the incidence rate of cancer was relatively higher in CKD patients than that in general population, which, mechanistically, may be related to chronic inflammation, accumulation of carcinogenic compounds, oxidative stress, impairment of DNA repair, excessive parathyroid hormone and changes in intestinal microbiota, etc. And in patients with cancer, regardless of tumor types or anticancer treatment, it has been indicated that the morbidity and incidence rate of concomitant CKD was also increased, suggesting a complex inter-relationship between CKD and cancer and arousing increasing attention from both nephrologists and oncologists. This narrative review focused on the correlation between CKD and cancer, and underlying molecular mechanisms, which might provide an overview of novel interdisciplinary research interests and the potential challenges related to the screening and treatment of CKD and cancer. A better understanding of this field might be of help for both nephrologists and oncologists in the clinical practice.